The Influence of Internal Control Systems on the Quality of Financial Reports of the Regional Secretariat of Balangan Regency - Kadir, Abdul; Amalia, Riezky; Audah, Ali; Leki, Rofinus (Universitas Hang Tuah, 2025)
This study aims to analyze the simultaneous and partial influence of the Control Environment, Risk Assessment, Control Activities, Information and Communication, and Internal Control Monitoring on the Quality of Financial Reports of the Balangan Regency Regional Secretariat. This study uses a quantitative approach with a causal associative research type, which aims to explain the causal relationship between independent and dependent variables. The study population consisted of 45 Civil Servants (PNS) of the Balangan Regency Regional Secretariat, with a saturated sampling technique, so that the entire population was sampled. Data analysis was carried out using Instrument Tests, Classical Assumption Tests, and Multiple Linear Regression. The results of the study indicate that: (1) simultaneously, the Control Environment, Risk Assessment, Control Activities, Information and Communication, and Internal Control Monitoring have a significant effect on the Quality of Financial Reports; (2) partially, the Control Environment, Risk Assessment, and Information and Communication have a significant effect, while Control Activities and Internal Control Monitoring do not have a significant effect on the Quality of Financial Reports; (3) The Control Environment is a variable that has a dominant influence on the Quality of Financial Reports.